PENGARUH PENERAPAN APLIKASI SISTEM INFORMASI MANAJEMEN DAN AKUNTANSI BARANG MILIK NEGARA (SIMAK BMN) TERHADAP EFEKTIVITAS PENGELOLAAN ASET NEGARA PADA BADAN NARKOTIKA NASIONAL (BNN) PROVINSI ACEH BIREUEN - admin; S, Muammar (JURNAL KEBANGSAAN, 2021)
This research was conducted to determine the effect of the Application of Sistem Informasi Manajemen dan Akuntansi Barang Milik Negara (SIMAK BMN) on the Effectiveness of State Asset Management at the National Narcotics Agency (BNN) in Aceh Province. The sample of this research was 33 respondents, consisting of the Head of the BNN work unit, the Head of the General Sub-Unit, and the Goods Manager at 11 Provincial and Regency/City in Aceh Province. The method of data analysis was simple linear regression analysis. The results of the study explain that the application of Sistem Informasi Manajemen dan Akuntansi Barang Milik Negara (SIMAK BMN) influenced the Effectiveness of State Asset Management at the Satker of the National Narcotics Agency (BNN) in Aceh Province. Indicators that need special attention so that the management of State Assets at the BNN work unit in Aceh Province can run effectively are operational and economic factors in implementing the SIMAK BMN application